A 352nW, 30 ppm/°C all MOS nano ampere current reference circuit. (November 2017) - Chouhan, Shailesh singh; Halonen, Kari
Abstract: In this work, an ultra low power all-MOSFET based current reference circuit, developed in 0.18 µm CMOS technology, is presented. The proposed circuit is based on the classical resistor-less beta multiplier circuit with an additional temperature compensation feature. The circuit is capable of providing the reference current in a nanoampere range for the supply voltage ranging from 1 V to 2 V in the industrial temperature range of −40 °C to 85 °C. The measurements were performed on 10 prototypes. The measured mean value of the reference current is 58.7 nA with a mean temperature coefficient value of 30 ppm/°C. In addition, the measured mean line regulation is 3.4%/V in the given supply voltage range. The total current consumption of the circuit is 352 nA and the chip area is 0.036 mm 2 .